2020
DOI: 10.46419/vs.51.6.10
|View full text |Cite
|
Sign up to set email alerts
|

Maternal microbiome during pregnancy and their impact on the canine microbiome in neonates

Abstract: The long-standing hypothesis that the neonatal microbiome is acquired during and after birth has been challenged by recent studies in humans using advanced molecular technologies, which identified bacteria and bacterial DNA and RNA in amniotic fluid, placenta, and meconium. Similar studies have recently been conducted on canine neonates, giving a description of the gut microbiota of newborn puppies and a comparison of different types of parturition on theirdevelopment. In this review, we summarize the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
2
1
Order By: Relevance
“…Moreover, literature research shows that the mammalian vagina contains a site-specific microbiota that holds a regulator and/or a drive essential role in many physiological and pathological processes in genital and reproductive health [24]. However, it is also shown that the vagina is much higher in richness but lower in diversity than the endometrium [5,21]. Interestingly, in the present study, the diversity of vaginal strains was richest in the postpartum group compared to the LSG group.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…Moreover, literature research shows that the mammalian vagina contains a site-specific microbiota that holds a regulator and/or a drive essential role in many physiological and pathological processes in genital and reproductive health [24]. However, it is also shown that the vagina is much higher in richness but lower in diversity than the endometrium [5,21]. Interestingly, in the present study, the diversity of vaginal strains was richest in the postpartum group compared to the LSG group.…”
Section: Discussioncontrasting
confidence: 38%
“…However, about 60% of the species in the vagina belong to the Hydrotalea, Ralstonia, Fusobacterium, or the Mycoplasma and Streptococcus genera [2, 5,10,20,21]. Nevertheless, concerning these reported data, our study identified only strains from the Burkholderia genera (i.e., Burkholderia cepacia).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation